Evaluation of T-Shaped Fins With a Novel Layout for Improved Melting in a Triple-Tube Heat Storage System - Ebrahimnataj Tiji, Mohammadreza; Mohammed, Hayder I.; Ibrahem, Raed Khalid; Dulaimi, Anmar; Mahdi, Jasim M.; Sh. Majdi, Hasan; Keshtkar, Mohammad Mehdi; Talebizadehsardari, Pouyan (Frontiers in Energy Research, 2022)
The effects of T-shaped fins on the improvement of PCM melting are numerically investigated in a vertical triple-tube storage containment. The PCM is held into the middle pipe of a triple-pipe heat exchanger while the heat transfer fluid flows through the internal and external pipes. The dimension effects of the T-shaped fins on the melting process of the PCM are investigated to determine the optimum case. The results indicate that, while using T-shaped fins improves melting performance of the PCM, the improvement potential is mainly governed by the fins body, rather than the fins head. Hence, the proposed T-shaped fin was unable to noticeably improve melting at the bottom of the PCM domain, a flat fin is added to the optimal case (Added-Fin case) and compared to the No-Fin, Uniform-Fin, and optimum T-shaped finned cases (no added fin). The analysis shows that the total heat storage rate of the added-Fin case increased by 141.7%, 58.8% and 47.6% compared with those of No-Fin, Uniform-Fin and the Optimum Cases, respectively. Furthermore, the total melting time for the Added-Fin case was 1882s and decreased by 59.6%, 38.4%, and 33.6% compared with those of the No-Fin, Uniform-Fin, and the Optimum Cases, respectively.